Active-type piezoelectric smart textiles with antifouling performance for pathogenic control - Lee, Su Eon; Lee, Hanna; Kim, Jang Hwan; Park, Jae Chul; Kyung, Sooah; Choi, Hayoung; Baek, Su Hyun; Park, Jun Hyun; Park, Sohyun; Kim, Jeong Min; Jo, Hye Jun; Cho, Seung Hyeon; et al. (npj Flexible Electronics, 2024)
Recently, an investigation into preventive measures for coronavirus disease 2019 (COVID-19) has garnered considerable attention. Consequently, strategies for the proactive prevention of viral pathogens have also attracted significant interest in the field of wearable devices and electronic textiles research, particularly due to their potential applications in personal protective equipment. In this study, we introduce smart textiles designed with optimized piezoelectric devices that exhibit antifouling performance against microorganisms and actively inactivate viruses. These active-type smart textiles, which incorporate advanced lead zirconate titanate (PZT) ceramics, a stretchable interconnector array, and polymeric fabric, demonstrate effective antifouling capabilities, detaching approximately 90% of Escherichia coli and 75% of SARS-CoV-2. Furthermore, they inactivate viruses, releasing ~26.8 ng of N protein from ruptured SARS-CoV-2, using ultrasonic waves within the wearable platform. Experimental results show that piezoelectric smart textiles significantly reduce the spread of COVID-19 by leveraging the electrical and acoustic properties of PZT ceramics.